AN EVALUATION OF URBAN PUBLIC TRANSPORT ROUTE. CASE STUDY: HOP-ON HOP-OFF, KUALA LUMPUR, MALAYSIA - Ismail, Izzati Khairimah; Hoon Leh, Oliver Ling; Ahmad Zaki, Zulkifli (PLANNING MALAYSIA, 2017)
Urban public transportation system is a means of providing mobility to locals, visitors as well as tourists. KL Hop-On Hop-Off buses, for instance, are designed specifically for local and foreign tourists to move within the Kuala Lumpur (KL) city centre areas for the purpose of tourism. However, there is only one route provided by the KL Hop-On Hop-Off, with more than 20 stops. The duration for a complete route tour without any stop is too long; that is around 2-2 Â½ hours. Coupled with the problem of traffic congestion in KL, passengers face the problems of punctuality and long waiting periods. Thus, this study was carried out to evaluate the existing route of the KL Hop-On Hop-Off bus services. GIS application and questionnaire survey were used to evaluate the route. As a result, this study proposes three new routes as the alternatives to the existing single route Hop-On Hop-Off bus service. With the new routes, duration of a single full route tour can be reduced based on the interest of tourist. Tourists will be able to concentrate on just one part of KL city centre for their one-day tour based on their interest either heritage, shopping or nature.